Variability in sclerotial morphology of Rhizoctonia solani f.sp. sasakii incitant of banded leaf and sheath blight of maize as revealed through Scanning Electron Microscope - and R.C. SHARMA, P. SRINIVAS, RASHMI AGGARWAL* (Indian Phytopathology, 2007)
Ten isolates of Rhizoctonia solani f.sp. sasakii collected from major maize growing areas showed morphological variability. With respect to colour of the colony two groups were observed, one having isolates from Bhuvaneshwar, Jorhat, Pusa, Delhi, Ludhiana, and Dhaulakuan and other group having isolates from Murorissa, Almora, Pantnagar and Karnal. Based on the pattern of sclerotial production, the isolates were also divided into two groups; one bearing peripheral sclerotia and other group having isolates bearing scattered sclerotia. SclerotiaI aggregation was observed in all the isolates, although more in Karnal isolate. Pantnagar isolate produced significantly higher weight sclerotia (1.71mg) than all isolates. SEM of sclerotia showed pits in isolates from Bhubaneshwar, Jorhat, Delhi, Ludhiana and Karnal. Surface texture as seen by SEM varied from compact to loose.